Inhibition of lncRNA TUG1 upregulates miR-142-3p to ameliorate myocardial injury during ischemia and reperfusion via targeting HMGB1- and Rac1-induced autophagy. (August 2019) - Su, Qiang; Liu, Yang; Lv, Xiang-Wei; Ye, Zi-Liang; Sun, Yu-Han; Kong, Bing-Hui; Qin, Zhen-Bai
Abstract: Background: Long non-coding RNAs (lncRNAs) play a central role in regulating heart diseases. In the present study, we examined the effects of lncRNA taurine up-regulated gene 1 (TUG1) in ischemia/reperfusion (I/R)- or hydrogen peroxide-challenged cardiomyocytes, with specific focus on autophagy-induced cell apoptosis. Methods: The expressions of miR-142-3p and TUG1 in H2 O2 -challenged cardiomyocytes and I/R-injured heart tissue were measured by RT-qPCR. Cell death was measured by trypan blue staining assay. Cell apoptosis was determined by Annexin V/PI staining and TUNEL assay. Autophagy was examined by quantifying cells or tissues containing LC3 + autophagic vacuoles by immunofluorescence, or by measuring the expressions of autophagy-related biomarkers by Western blot. The direct interaction between miR-142-3p and TUG1, high mobility group box 1 protein (HMGB1), or Ras-related C3 botulinum toxin substrate 1 (Rac1) was examined using luciferase reporter assay. The significance of miR-142-3p and TUG1 on cell apoptosis or autophagy was examined using both gain-of-function and loss-of-function approaches. The importance of HMGB1 or Rac1 was assessed using siRNA-mediated gene silencing. Results: miR-142-3p was down-regulated, while TUG1 up-regulated in H2 O2 -challenged cardiomyocytes in vitro and I/R-injured heart tissues in vivo. Functionally, inhibition of TUG1 and overexpression of miR-142-3p inhibited cell apoptosis and autophagy in cardiomyocytes. The function of TUG1 were achieved by sponging miR-142-3p and releasing the suppression of the putative targets of miR-142-3p, HMGB1 and Rac1. Both HMGB1 and Rac1 essentially mediated cell apoptosis and autophagy induced by TUG1. Conclusions: TUG1, by targeting miR-142-3p and up-regulating HMGB1 and Rac1, plays a central role in stimulating autophagic cell apoptosis in ischemia/hypoxia-challenged cardiomyocytes. Down-regulating TUG1 or up-regulating miR-142-3p may ameliorate myocardial injury and protect against acute myocardial infarction.